Lacanian Materialism and the Question of the Real - Eyers, Tom (Cosmos and History: The Journal of Natural and Social Philosophy, 2011)
This article attempts to explain the ambiguous association of Lacanian psychoanalysis with materialism. Resisting attempts to divide Lacan’s work into discrete periods, I argue that, throughout his work, Lacan was concerned with articulating aspects of language and subjectivity that resist incorporation into networks of idealised meaning or sense, and that it is this emphasis on the materiality of language, routed through the concept of the Real, that makes up the particular ’materialism’ of Lacanian theory. The emergence of this strain of thinking is located in Lacan’s radical reworking of Freud’s theses on primary narcissism.